2021
DOI: 10.3390/jpm11050332
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinformatics Analysis Identifies the Telomerase Inhibitor MST-312 for Treating High-STMN1-Expressing Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a relatively chemo-resistant tumor. Several multi-kinase inhibitors have been approved for treating advanced HCC. However, most HCC patients are highly refractory to these drugs. Therefore, the development of more effective therapies for advanced HCC patients is urgently needed. Stathmin 1 (STMN1) is an oncoprotein that destabilizes microtubules and promotes cancer cell migration and invasion. In this study, cancer genomics data mining identified STMN1 as a prognosis biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In addition, treatment with MST-312 resulted in a high number of senescent cells, as measured by senescence-associated β-galactosidase staining ( 12 ). Furthermore, a recently published study indicated that MST-312 was a potent inhibitor of hepatocellular carcinoma (HCC) cells that overexpressed stathmin 1, an oncoprotein that promotes cancer cell migration and invasion ( 13 ). However, the precise mechanisms of telomerase inhibition by MST remain unclear ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, treatment with MST-312 resulted in a high number of senescent cells, as measured by senescence-associated β-galactosidase staining ( 12 ). Furthermore, a recently published study indicated that MST-312 was a potent inhibitor of hepatocellular carcinoma (HCC) cells that overexpressed stathmin 1, an oncoprotein that promotes cancer cell migration and invasion ( 13 ). However, the precise mechanisms of telomerase inhibition by MST remain unclear ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic and natural inhibitors are the molecules that play a significant role in telomerase inhibition, either by directly blocking the enzymatic subunits (such as MST-312, BIBR1532 etc.) or by blocking the formation of the enzymatic entity through the inhibition of the translation process ( 13 , 14 ). Synthetic drugs that bind to the template region of telomerase, such as imetelstat, have already begun to be tested in both in vivo and in vitro experiments; of note, impressive results have been obtained in several cancer types (melanoma, glioblastoma and pancreatic carcinoma, etc.)…”
Section: Discussionmentioning
confidence: 99%
“… 35 Stathmin 1ʹs importance for hepatoma seems to be on the rise, since it has recently been proposed as a tumorigenic and progression regulator due to its interaction with YAP1, 36 and, when overexpressed, as a novel treatment target for HCC. 37 Furthermore, sorafenib and regorafenib shared the “Synaptic Long-Term Depression” pathway, which is not surprising given that it encompasses the activation of glutamate and other neurotransmitter receptors, 38 as seen in the KEGG neuroactive ligand/receptor enriched set. Additionally, we found the “Hepatic Fibrosis/Hepatic Stellate Cell Activation” in both the sorafenib and lenvatinib responders and “Calcium Signalling” in the cabozantinib and “regorafenib over sorafenib” groups.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, HCC is a prominent multifactorial disease with numerous etiologies making broad-spectrum chemotherapies and treatments unreliable, thereby necessitating precision therapies. Bioinformatics and multi-omic approaches that identify biomarkers and therapeutic targets such as stathmin-1, HGF, and miR-29a may be the key to realizing true therapeutic results with precision therapies in specific subclasses of HCC [ 5 , 6 , 7 ]. Wang et al show that using the telomerase inhibitor MST-312 could attenuate viability and decrease migration and invasion capabilities of stathmin-1-high expression HCCs [ 6 ].…”
mentioning
confidence: 99%
“…Bioinformatics and multi-omic approaches that identify biomarkers and therapeutic targets such as stathmin-1, HGF, and miR-29a may be the key to realizing true therapeutic results with precision therapies in specific subclasses of HCC [ 5 , 6 , 7 ]. Wang et al show that using the telomerase inhibitor MST-312 could attenuate viability and decrease migration and invasion capabilities of stathmin-1-high expression HCCs [ 6 ]. Crisper/CAS9 gene editing holds promise for precision therapeutic interventions to reprogram diseases cells.…”
mentioning
confidence: 99%